(untitled) (ModaPalavra e-periódico, 2017)
This research focuses on the clothing industry in the Pato Branco city, highlighting aspects related to management, design, characterization of raw materials and generation of waste. In the present study, a diagnosis was made with the companies, with the purpose of obtaining information on their profiles, highlighting the management, design and development of the product, raw materials used and generation of textile waste. These companies are characterized as micro and small enterprises, operating in different market segments, with a strong tendency to produce professional uniforms. As a result, much of the waste generated is knitted scraps. In this sense, an alternative for the reuse of these wastes could contribute from the environmental point of view by means of a better targeting of these, as well as economically, since they could be directed towards the production of products of greater added value.